Unveiling Spiritual Guidance: Sheikh Muhammad Waly al-Khalidy’s Role in Naqshbandiyah Sufi Order in Aceh - Wirianto, Dicky; Manan, Abdul; Zubaidah, Zubaidah; Suraiya, Suraiya (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This article critically explains the concept and practice of the spiritual initiation (rābiṭah murshid) of the disciple and the role of Sheikh Muhammad Waly al-Khalidy in the Naqshbandiyah (Sufi) order in Aceh. Employing a qualitative method along with a hermeneutical approach the research found that the role of the guide is at the core of spiritual training and education. The spiritual connection between the student and the teacher is an intimate bond that allows the latter to guide the former in his efforts to become a perfect human being. The findings of this study differ from those of J. Spencer Trimingham, Julia Day Howell, and Mulyadhi Kartanegara who assumed that the authority of the spiritual guide is overemphasized and no longer necessary once the sālik reached his path. However, according to Muhammad Waly, a true sheikh has natural authority, and this authority is justified and does not intrude upon the Shari‘ah as it has been done during the reading of Naẓam of Obat Hati (Medicine of the Heart) containing the names of the murshids and khulafā’ of the Sufi order.